(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This study investigates the influence of formative assessment practices on student motivation, particularly in secondary English language classrooms. Using a mixed-methods approach involving surveys, semi-structured interviews, and classroom observations, the study identifies key ways in which feedback, peer assessment, and self-assessment practices contribute to increased student engagement and motivation. The results indicate that when formative assessment is integrated purposefully, it enhances both intrinsic and extrinsic motivation. This paper contributes to a growing body of literature supporting the pedagogical shift toward formative, learner-centered assessment.